SUPERVISORS’ RATING OF COMPETENCIES POSSESSED BY OFFICE TECHNOLOGYAND MANAGEMENT GRADUATEWORKERS IN PUBLIC ORGANISATIONS IN KATSINASTATE (NAU Journal of Technology and Vocational Education, 2024)
This research was necessitated by dividedly reported lack of relevant competencies byOffice Technology and Management graduates by employers. It determines supervisors'rating of competencies possessed by OTM graduates working in public organisations inKatsina State. Two research questions guided the study and two null hypotheses weretested at 0.05 level of significance. The population of the study comprised 248 supervisorsin public organisations. Instrument used for data collection was a 36 items questionnairevalidated by of experts. The internal consistency of the items was ensured through split halfmethod and Pearson Product Moment Co-relation Co-efficient was used to determine thereliability. Mean ratings and standard deviations were used to answer the researchquestions while z-test was used to test the null hypotheses. Findings revealed that OTMgraduates possessed word processing competencies to a great extent and desktoppublishing competencies at a low extent. Gender did not significantly significantlyinfluence respondents' mean ratings as the extent OTM graduates workers possessedword processing competencies but type of organisation significantly influenced therespondents' mean ratings as the extent workers possessed desktop publishingcompetencies. Based on the findings, it was recommended among others that OTMgraduatesshould begivenadequate trainingondesktop publishing.